MEASURES OF MIGRATION REGURATION AND THEIR SOCIO-ECONOMIC RESULTS: WORLD EXPERIENCE - MULSKA, OLHA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Based on the analysis of world experience, it is determined that the task of state policy on migration management is to develop effective tools for migration management to maximize potential benefits (employment, increase national income, increase the competitiveness of the national economy, strengthen intellectual and security, ensure tax revenues) and minimization of possible costs, risks and threats (economic exploitation, distant families, social orphanhood, 'immigrant ghetto', labour shortages, loss of potential tax revenue, increasing social inequality, brain drain, loss of investment in human capital, R&D inflation).The aim of the article is to highlight the tasks and tools of the state policy of regulating migration transfers in the context of stimulating the socio-economic development of the country based on world experience.An important strategic goal of the policy is to ensure stable potential remittances by migrants for economic progress, which is a challenge for developing countries in the context of globalization, as emigrants are not always investors in the national economy, small and medium businesses, and social capital. A significant proportion of migrant workers remain permanently resident in the country of destination, severing all social contacts with the donor country. From the point of view of state policy, the most constructive approach to the management of migration processes is one that, under specific conditions or factors of influence, is favourable for the use of administrative-political and organizational-economic instruments. One of the barriers to the implementation of measures of regulating migration processes is the gap between the economy, on the one hand, and a well-oriented financial and institutional system, on the other. Accounting and quasimetric of remittances, assessment of their impact on economic development, formation, and implementation of policies to reduce transfer costs and integrate migration transfers into real sectors of the economy require the development of additional tools to regulate the development of innovation-oriented economy.
Keywords: migration processes; tools; economic effects; migration transfers; efficiency; migration corridor